2014
DOI: 10.1111/irv.12276
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase and caspase activity in nasopharyngeal secretions are predictors of bronchiolitis severity

Abstract: BackgroundBronchiolitis is the leading cause of hospitalization in infants. Biomarkers of disease severity might help in clinical management.ObjectiveTo determine the clinical predictiveness of NW-LDH, NW-caspase 3/7, and NW-LDH/NW-caspase 3/7 ratio in bronchiolitis.MethodsPreviously healthy children less than 24 months of age with bronchiolitis were recruited from the Texas Children's emergency room and intensive care unit from October 2010 to April 2011. Demographic, clinical information, and NW samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…Findings from this study have been previously reported [13, 15]. Healthy children less than 24 months of age without a known co-morbid condition who presented to the ED with respiratory distress and were diagnosed with bronchiolitis by their attending physician were eligible for study participation [13].…”
Section: Methodsmentioning
confidence: 91%
“…Findings from this study have been previously reported [13, 15]. Healthy children less than 24 months of age without a known co-morbid condition who presented to the ED with respiratory distress and were diagnosed with bronchiolitis by their attending physician were eligible for study participation [13].…”
Section: Methodsmentioning
confidence: 91%
“…Also, apposite to the findings of this study, the study of Rahman et al in 55 children over 6months of age with bronchiolitis found a straight relationship between the concentration of LDH of NW and the outcomes of bronchiolitis in children. 5 In their study LDH concentration of NW had a significant positive correlation with the severity of the disease, duration of hospitalization and the duration of oxygen therapy which can be due to fewer newborns and limitation in age up 6months.…”
Section: Discussionmentioning
confidence: 89%
“…4 The study by Mehta et al in the United States showed that LDH concentration in the NW in children aged 4 to 12months has an inverse relationship with the risk of admission but in the 12-24month children with a straight relationship was at risk of being hospitalized. 5 The study of Rahman et al in Egypt also showed that there was a significant straight relationship between the LDH concentration in NW in children older than 6months with severity of bronchiolitis, duration of hospitalization and oxygen therapy. 6 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In view of this, we postulate that our clinical predictive model may improve with the addition of nasal biomarkers. Nasal wash lactate dehydrogenase and nasal wash caspase were previously reported to value add in predicting bronchiolitis severity, specifically those requiring intensive care monitoring . While these remain exploratory, they hold potential to strengthen the robustness of prediction models.…”
Section: Discussionmentioning
confidence: 99%